Remarks on the Anathemas in the "Palaea Historica" - Skowronek, Małgorzata; Majer, Marek (Studia Ceranea, 2013)
The original text of the Palaea Historica, a Byzantine narration based on the initial books of the Old Testament, contains two anathema directed against the Phundagiagitae (adherents of a medieval neo-Manichaean heresy), accusing them of the belief in Cain’s being the son of Satanael and in that the union of Adam and Eve occurred in the Garden of Eden already. The analysis of the relevant passages and their counterparts in two Slavic translations of the Palaea, as well as certain other Byzantine and Slavic medieval texts with related content, contributes to illuminating the circumstances under which the Slavic translations arose. The paper also discusses the very term Phundagiagitae (practically absent from all other Slavic sources) and addresses the issue of the supposed non-canonicity of the Palaea.